HAYDÉE GUANAIS DOURADO FAZ CEM ANOS: APRENDENDO COM A HISTÓRIA - Meira de Melo, Cristina Maria; Silva, Gilberto Tadeu Reis da; Costa, Heloniza Oliveira Gonçalves (Revista Baiana de Enfermagem‏, 2015)
EDITORIAL